Student Empathy in Terms of Gender Differences - Imallatul Istma; Daharnis Daharnis (Consilium, 2022)
Empathy ability is very important for every individual, especially in terms of interacting with the social environment, but students can still be found who have low empathy skills when interacting with their surroundings, especially in the school environment. This study aims to describe student empathy and differences in student empathy in terms of gender. This research uses a quantitative method with a comparative descriptive research type. The population in this study were students in class X and XI SMKN 6 Padang in the 2022/2023 school year with a total of 489 students and a sample of 251 students using proportional random sampling. Collecting data in this study using a student empathy questionnaire. Data were processed using descriptive analysis and t-test with the help of SPSS version 20. The results showed that the empathy of students at SMKN 6 Padang was in the "high" category with a percentage of (78.3%). There is a significant difference between students' empathy in terms of gender. The percentage of empathy between male students (76.52%) and female students (79.6%) with a significance value (2-tailed) of 0.000. The results of this study have implications for Guidance and Counseling service activities.